EFFECTIVENESS OF IMPLEMENTATION OF IT ENHANCED PEDAGOGY IN BUSINESS SCHOOLS IN DELHI – NCR - Anupama R and Sanjeev Bansal (Abhigyan, 2013)
Instructional Technology has indeed been a catalyst for change. This study deals with relevance and impact of IT on the current educational systems. Correct data analysis can lead to optimal solutions so that we can augment the benefits of IT enhanced education on student achievement. A validated questionnaire after testing for its reliability was administered to business school students of Delhi-NCR region. It was ensured that there was fair representation of both private and government institutions. The initial descriptives indicated that students were willing to spend small amounts of money on internet use. A simple t-test revealed that students were willing to study the easier part of the syllabi online but wanted a healthy interaction with the instructors who were probably viewed as “emotional crutches”, for clarifications, feedback, and removal of doubts and anxieties. Class capture systems were found to be moderately useful due to slow downloads. An independent sample t-test yielded complete gender equity in all variables of perception, attitude and preferences towards technology use except on the variable “ease of learning”. So we must ensure that enough training and support is provided before any implementation. Change management should be structured such that the strengths of both genders can be suitably utilized.